Simulasi co-combustion batubara dan biomassa tandan kosong kelapa sawit tertorefaksi (torrefied biomass) - Zaenal Arifin; Amrul Amrul; Muhammad Irsyad (TURBO [Tulisan Riset Berbasis Online], 2021)
Coal is still widely used as the main fuel in the industry, especially the power generation industry (PLTU), cement plants and etc. Coal is a fossil fuel whose availability is thinning and its fires produce CO2 emissions that cause a rise in greenhouse gas (GHG) concentricity. On the other biomass is an alternative energy source that is abundant, including empty bunches of oil palm (TKKS), but has poor combustion properties compared to coal when burned directly. The properties of biomass burning can be improved by certain treatment, one of which is through the process of torrefaction. Biomass torrefaction has a calorific value equivalent to sub-bituminous coal B, so it has the potential to be used as an alternative fuel for coal. The purpose of this study was to determine the maximum temperature that occurs in the burner. In this study co-combustion was conducted on simulation of ANSYS program with powder system (pulverized combustion) because this type in recent decades is widely used in industry. In this study conducted a simulation on ANSYS to determine the temperature on the burner and the concentration of emissions produced. The results showed that the simulation of co-combustion burner burner showed the maximum temperature reached 970°C.  The effect of burner and burner temperature in the form of swirl provides sufficient oxygen with more perfect combustion resulting in decreased concentration of CO2 emissions and low concentration of N2 due to higher nozzle temperature. High temperatures lower the concentration of SO2 in the burn chamber.Keyword: Co-combustion, pulverized co-combustion simulation, TKKS torrefaction, burner.